Overcoming Learning Boredom through Digital Game-Based Learning - Qomar, Aulia Hanifah; Refai, Refai; Mahendra, I Nyoman Aditya; Rahmadani, Zharifa Putri; Lolita, Inggita Rantya; Kusumawati, Fitri Palupi (Linguapedia, 2025)
This study investigates the implementation of Digital Game-Based Learning (DGBL) as a creative solution to reduce learning boredom at Yos Sudarso Metro High School. It explored the impact of game-based tools on student engagement, motivation, and understanding during the learning process. This research employed a qualitative method, with data collected through classroom observations and Google Forms questionnaires. The data were analyzed using Qualitative Thematic Analysis to identify recurring patterns in students’ experiences. The findings indicated three main themes, namely increased student engagement, perceived effectiveness of digital game platforms, and challenges in implementation. Platforms such as Quizizz and Wordwall encourage interactive and enjoyable learning, leading to improved comprehension, particularly in English subjects. This qualitative study involved 32 eleventh-grade students selected through purposive sampling, with data collected through classroom observations and a structured questionnaire.  However, limitations such as unequal access to technology and inconsistency in tool effectiveness remain obstacles. The study concludes that DGBL is a promising approach to minimize learning boredom and fostering a more dynamic, student-centered learning environment. These results suggest that integrating game-based tools into classroom instruction can enhance participation and learning outcomes, provided that implementation challenges are addressed with proper planning and resources